Tindak Tutur Ekspresif Guru dalam Pembelajaran Surat Dinas dan Surat Pribadi di Kelas VII SMP Negeri 2 Suliki Kabupaten Lima Puluh Kota - Luckiansyah, Geri; Abdurahman, Abdurahman (Lembaga Yasin AlSys, 2023)
There are three objectives of this research. First, it describes what forms of expressive speech acts are used by Indonesian language teachers in the process of learning official letters and personal letters in class VII of SMP Negeri 2 Suliki, Lima Puluh Kota Regency. Second, it describes the Indonesian teacher's speaking strategies in the process of learning official letters and personal letters in class VII of Suliki 2 Public Middle School, Fifty City District. This type of research is a qualitative research with descriptive method. The data in this study were sentences in the form and expressive speech act strategies of the Indonesian language teacher for grade VII SMP Negeri 2 Suliki, Fifty Cities Regency, in the learning process. The data source for this research is all the utterances of one Indonesian language teacher during the teaching and learning process from the beginning to the end of the lesson. The results of this study are twofold. First, there are five forms of expressive speech acts for teachers in learning official letters and personal letters in class VII SMP Negeri 2 Suliki, Fifty Cities District, (1) expressive speech acts of praising, (2) expressive speech acts of saying thank you, (3) expressive speech acts expressive speech act of criticizing, (4) expressive speech act of blaming, and (5) expressive speech act of apologizing. Second, the teacher's speaking strategy in learning official letters and personal letters in class VII of SMP Negeri 2 Suliki, Fifty Cities Regency, there are four, (1) a strategy of speaking frankly without preamble, (2) a strategy of speaking frankly with positive politeness, (3) the strategy of speaking frankly with negative politeness, and (4) the strategy of speaking vaguely.